Geometry for dummies: 1001 practice problems with free online practice - Ma, Allen; Kuang, Amber (Hoboken, NJ : John Wiley & Sons, Inc., 2015)
Practice makes perfect, and this friendly guide, with free access to online problems, gives you 1,001 chances to practice core geometry concepts! Perfect your skills with points, lines, angles, planes, and the area and volume of shapes. Polish up proofs, theorems, and postulates. You can track your progress online and see where you need more study. As your skills grow, so will your confidence!
Includes index.
Keywords: Geometry -- Problems, exercises, etc